Ablation of CNTN2+ Pyramidal Neurons During Development Results in Defects in Neocortical Size and Axonal Tract Formation - Kastriti, Maria Eleni; Stratigi, Aikaterini; Mariatos, Dimitris; Theodosiou, Marina; Savvaki, Maria; Kavkova, Michaela; Theodorakis, Kostas; Vidaki, Marina; Zikmund, Tomas; Kaiser, Jozef; Adameyko, Igor; Karagogeos, Domna (Frontiers in Cellular Neuroscience, 2019)
Corticothalamic axons express Contactin-2 (CNTN2/TAG-1), a neuronal recognition molecule of the immunoglobulin superfamily involved in neurogenesis, neurite outgrowth and fasciculation. TAG-1, which is expressed transiently by cortical pyramidal neurons during embryonic development, has been shown to be fundamental for axonal recognition, cellular migration and neuronal proliferation in the developing cortex. Although Tag-1-/- mice do not exhibit any obvious defects in the corticofugal system, the role of TAG-1+ neurons during the development of the cortex remains elusive. We have generated a mouse model expressing EGFP under the Tag-1 promoter and encompassing the coding sequence of Diptheria Toxin subunit A (DTA) under quiescence with no effect on the expression of endogenous Tag-1. We show that while the line recapitulates the expression pattern of the molecule, it highlights an extended expression in the forebrain, including multiple axonal tracts and neuronal populations, both spatially and temporally. Crossing these mice to the Emx1-Cre strain, we ablated the vast majority of TAG-1+ cortical neurons. Among the observed defects were a significantly smaller cortex, a reduction of corticothalamic axons as well as callosal and commissural defects. Such defects are common in neurodevelopmental disorders, thus this mouse could serve as a useful model to study physiological and pathophysiological cortical development.